Kriteria fajar Sadiq perspektif ilmu falak - Nurlaelah Syarifuddin; Alimuddin; Sholeh Ridwan (Universitas Islam Negeri Alauddin Makassar, 2023)
The main problem of this research for To find out the prophet’s instructions about the dawn of sadiq?Sub problem how to from the perspective of astronomy? To find out the dawn of sadiq according to astronomy. This type of research with the nature of “library research” with syar’i, philosophical, and astronomical approaches.The results of this study that time for the dawn prayer entered the category .of down shadiq, namely the second dawn until the end of the dark night because the prophet Muhammad used to do the.dawn prayer ending until sunrise. Some mass organizations concluded that the criteria for fajar shadiq and some astronomy lecturers were different, starting with the nahdatul ulama who determined that -18 degrees were originally .-20 degrees, this is also used by the ministry of religion, which is -18 degrees, while the view of astronomy lecturers is based on the same movement. Conducted on research in jakarta and yogyakarta from the results of these studies they found -18 to -18.This study focuses on the criteria for the dawn of sadiq and the beginning of the dawn prayer time. This research is in the form of literature that can be influnced by several comples factors, therefore it is hoped that astronomy academics and competent instituons can conduct contemporary research in accordance with modern science as a whole at the point where there may be differences in the results of fajar shadi’s criteria.